2016
DOI: 10.1017/s0954579416000122
|View full text |Cite
|
Sign up to set email alerts
|

Maternal physiological dysregulation while parenting poses risk for infant attachment disorganization and behavior problems

Abstract: The extent to which indices of maternal physiological arousal (skin conductance augmentation) and regulation (vagal withdrawal) while parenting predict infant attachment disorganization and behavior problems directly or indirectly via maternal sensitivity was examined in a sample of 259 mothers and their infants. Two covariates, maternal self-reported emotional risk and AAI attachment coherence were assessed prenatally. Mothers’ physiological arousal and regulation were measured during parenting tasks when inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 74 publications
(115 reference statements)
4
35
0
Order By: Relevance
“…(López Seco et al 2016). Mothers´arousal and regulation while parenting interacted to predict infant attachment disorganization and behavior problems (Leerkes et al 2017). Also, the interaction of insecure attachment and behavioral inhibition increased the risk for internalizing problems such as anxiety (Lewis-Morrarty et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…(López Seco et al 2016). Mothers´arousal and regulation while parenting interacted to predict infant attachment disorganization and behavior problems (Leerkes et al 2017). Also, the interaction of insecure attachment and behavioral inhibition increased the risk for internalizing problems such as anxiety (Lewis-Morrarty et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…These subtle variations in caregiving quality are difficult to observe, but they may affect infant stress arousal and regulation via the synchrony of bodily rhythms between mother and infant (Feldman, 2007). It has been proposed that this may in turn contribute to maladaptive infant outcomes (Leerkes, Su, O’Brien, Calkins, & Supple, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Yet another potential factor disrupting the caregiver's ability to regulate is the caregiver's physiology (Leerkes, Su, Calkins, O'Brien, & Supple, 2017;Lorber & O'Leary, 2005). For instance, one study found that increases in mothers' self-reported depressive symptomology was associated with increased infant cortisol responses to a stressor, but only if the mother also had high levels of cortisol .…”
Section: Maternal Regulation Of Child Stress Responsementioning
confidence: 99%
“…For instance, one study found that increases in mothers' self-reported depressive symptomology was associated with increased infant cortisol responses to a stressor, but only if the mother also had high levels of cortisol . Indeed, other studies have found that maternal physiology may be unrelated to self-report and/or observed parenting measures, yet still related to the child's physiology (Emery, McElwain, Groh, Haydon, & Roisman, 2014;Leerkes et al, 2017;Luecken, Crnic, Gonzales, Winstone, & Somer, 2018). This idea is consistent with Hofer's "hidden regulators" hypothesis in which he identified mechanisms in the mother-child relationship that "were not evident when simply observing the ongoing mother-infant relationship," but regulated child behavior and physiology (Hofer, 2010, p. 157).…”
Section: Maternal Regulation Of Child Stress Responsementioning
confidence: 99%